PENERAPAN MEDIA SIMULASI VIRTUAL UNTUK MENINGKATKAN PENGUASAAN KONSEP LISTRIK DINAMIS MELALUI PEMBELAJARAN KONTEKSTUAL DI SMAN 4 PEKANBARU - Rahmawati '; Muhammad Nasir; Ma’aruf ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aims this study to determine the incresing dynamic electric concepts with the application of virtual simulation media through contextual learning in class X SMAN 4 Pekanbaru. The subjects were students of class X1 and X2 class. X1 class as a class experiment with the number of students by 37 votes, while class X2 as the control class with the number of students as many as 37 people. Data collection instrument in this research is test the mastery of concept of dynamic electric that consists of 10 items essay. Analysis of the data in this research is descriptive analysis to see the picture of increasing mastery of the concept of dynamic electricity students by using the value of the gain is normalized and inferential analysis to know there is no difference between the classes who use the virtual simulation media through contextual learning with classes that do not use the application virtual simulation media of the dynamic electric concept mastery. From the analysis of the data shows: the value of the gain is normalized experimental class was 0.76 with a high category, while the value of the normalized gain control group was 0.71 with a high category and there value significance 0,765>0,05 and (3,482>2,028) so accepted, meaning there is a difference between a class that uses the application of virtual simulation media through contextual learning with classes that do not use the media application of virtual simulation of the dynamic electric concept mastery. Thus, it can be concluded that the application of virtual simulation media through contextual learning can be used for learning in class X1 SMAN 4 Pekanbaru.Key Words: virtual simulation media, contextual learning, mastery of concepts, dynamic electric